Ligand-dependent stereoselective Suzuki–Miyaura cross-coupling reactions of β-enamido triflates - Chvojka, Tomáš; Markos, Athanasios; Voltrová, Svatava; Pohl, Radek; Beier, Petr (Beilstein Journal of Organic Chemistry, 2021)
The stereoselective Suzuki–Miyaura cross-coupling of (Z)-β-enamido triflates is demonstrated. Depending on the nature of the ligand in the palladium catalyst, either retention or inversion of the configuration during the synthesis of β,β-diaryl-substituted enamides is observed. Thus, the method provides synthetic access to both isomers of the target enamides from (Z)-β-enamido triflates.
Keywords: enamides; isomerization; Suzuki–Miyaura coupling; vinyl triflates

(untitled) - Gopalaiah, K.; Kagan, H. B. (Chem. Rev., 2011)

(untitled) - Beltran, F.; Miesch, L. (Synthesis, 2020)

(untitled) - Zhao, B.; Shang, R.; Wang, G.-Z.; Wang, S.; Chen, H.; Fu, Y. (ACS Catal., 2020)

(untitled) - Zhang, W.-W.; Zhang, S.-L.; Li, B.-J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Zhang, G.; Zhou, S.; Fu, L.; Chen, P.; Li, Y.; Zou, J.; Liu, G. (Angew. Chem., Int. Ed., 2020)

(untitled) - Zhen, L.; Tong, S.; Zhu, J.; Wang, M.-X. (Chem. – Eur. J., 2020)

(untitled) - Liu, R.-H.; Shen, Z.-Y.; Wang, C.; Loh, T.-P.; Hu, X.-H. (Org. Lett., 2020)

(untitled) - Bai, X.-Y.; Zhao, W.; Sun, X.; Li, B.-J. (J. Am. Chem. Soc., 2019)

(untitled) - Friedfeld, M. R.; Zhong, H.; Ruck, R. T.; Shevlin, M.; Chirik, P. J. (Science, 2018)

(untitled) - Martín, M. J.; Coello, L.; Fernández, R.; Reyes, F.; Rodríguez, A.; Murcia, C.; Garranzo, M.; Mateo, C.; Sánchez-Sancho, F.; Bueno, S.; de Eguilior, C.; Francesch, A.; et al. (J. Am. Chem. Soc., 2013)

(untitled) - Lin, S.; Yang, Z.-Q.; Kwok, B. H. B.; Koldobskiy, M.; Crews, C. M.; Danishefsky, S. J. (J. Am. Chem. Soc., 2004)

(untitled) - Shen, R.; Lin, C. T.; Bowman, E. J.; Bowman, B. J.; Porco, J. A. (J. Am. Chem. Soc., 2003)

Amination and Formation of sp2 C-N Bonds - Correa, A.; Bolm, C. (Metal-Catalyzed C(sp2)–N Bond Formation, 2013)

(untitled) - Arndt, M.; Salih, K. S. M.; Fromm, A.; Goossen, L. J.; Menges, F.; Niedner-Schatteburg, G. (J. Am. Chem. Soc., 2011)

(untitled) - Gooßen, L. J.; Salih, K. S. M.; Blanchot, M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Herrero, M. T.; de Sarralde, J. D.; SanMartin, R.; Bravo, L.; Domínguez, E. (Adv. Synth. Catal., 2012)

(untitled) - Minko, Y.; Pasco, M.; Lercher, L.; Botoshansky, M.; Marek, I. (Nature, 2012)

(untitled) - Mallick, R. K.; Prabagar, B.; Sahoo, A. K. (J. Org. Chem., 2017)

(untitled) - Baldassari, L. L.; de la Torre, A.; Li, J.; Lüdtke, D. S.; Maulide, N. (Angew. Chem., Int. Ed., 2017)

(untitled) - Trost, B. M.; Cregg, J. J.; Quach, N. (J. Am. Chem. Soc., 2017)

(untitled) - Markos, A.; Voltrová, S.; Motornov, V.; Tichý, D.; Klepetářová, B.; Beier, P. (Chem. – Eur. J., 2019)

(untitled) - Markos, A.; Janecký, L.; Klepetářová, B.; Pohl, R.; Beier, P. (Org. Lett., 2021)

(untitled) - Markos, A.; Janecký, L.; Chvojka, T.; Martinek, T.; MartinezSeara, H.; Klepetářová, B.; Beier, P. (Adv. Synth. Catal., 2021)

(untitled) - Wang, T.; Tang, Z.; Luo, H.; Tian, Y.; Xu, M.; Lu, Q.; Li, B. (Org. Lett., 2021)

(untitled) - Lu, G.-P.; Voigtritter, K. R.; Cai, C.; Lipshutz, B. H. (J. Org. Chem., 2012)

(untitled) - Feceu, A.; Sangster, L. E.; Martin, D. B. C. (Org. Lett., 2018)

(untitled) - Chehal, N. K.; Budzelaar, P. H. M.; Hultin, P. G. (Org. Biomol. Chem., 2018)

(untitled) - Molinaro, C.; Scott, J. P.; Shevlin, M.; Wise, C.; Ménard, A.; Gibb, A.; Junker, E. M.; Lieberman, D. (J. Am. Chem. Soc., 2015)

(untitled) - Li, B. X.; Le, D. N.; Mack, K. A.; McClory, A.; Lim, N.-K.; Cravillion, T.; Savage, S.; Han, C.; Collum, D. B.; Zhang, H.; Gosselin, F. (J. Am. Chem. Soc., 2017)

(untitled) - Trost, B. M.; Tracy, J. S. (ACS Catal., 2019)